A review on diamond-like carbon-based films for space tribology. Issue 15 (13th October 2022) - Shi, Bang; Wu, Yanxia; Liu, Ying; Wang, Limin; Gao, Jie; Hei, Hongjun; Zheng, Ke; Yu, Shengwang
ABSTRACT: Space solid lubricants should undergo serious tests, such as high pressure, high vacuum, strong radiations and so on. Diamond-like carbon (DLC) films show potential applications in space because of low friction in vacuum. However, the short sliding lifetime should be a critical issue, and many methods are used to improve it. This paper highlights the development and broad potential of DLC films with special structures used in vacuum. The frictional behaviours of DLC-based films in other space conditions, such as radiation and extreme temperatures, are also addressed. Furthermore, the tribological performances and related mechanisms under different environments are discussed. Finally, some open issues concerning space applications are discussed.